Geographical discrimination of olive oils from Cv. 'Galega Vulgar' - Rodrigues, Nuno (2021)
Olive oils from seven Portuguese regions were selected to study the effect of the geographical origin on the oils' composition. Quality parameters, fatty acids, tocopherols, hydroxytyrosol and tyrosol derivatives, and oxidative stability were evaluated. All olive oils could be classified as extra virgin, and the geographical origin significantly affected the oils chemical composition. Principal component analysis further confirmed the significant impact of the geographical origin on the composition and, indirectly, on stability of the oils, showing that the evaluated parameters could be used as markers for geographical origin identification. Alternatively, Fourier transform infrared spectroscopy was applied, allowing to establish a linear discriminant model that correctly identified the geographical origin of the olive oils with a mean sensitivity of 99 +/- 3 % (internal validation), confirming the impact of the oil origin on its characteristics. This finding allowed foreseeing the future application of the spectroscopy approach as a green, fast and non-invasive authentication tool.